Admission blood glucose predicted haemorrhagic shock in multiple trauma patients. Issue 1 (January 2015) - Kreutziger, Janett; Rafetseder, Andreas; Mathis, Simon; Wenzel, Volker; El Attal, René; Schmid, Stefan
Abstract: Introduction: Admission blood glucose is known to be a predictor for outcome in several disease patterns, especially in critically ill trauma patients. The underlying mechanisms for the association of hyperglycaemia and poor outcome are still not proven. It was hypothesised that hyperglycaemia upon hospital admission is associated with haemorrhagic shock and in-hospital mortality. Methods: Data was extracted from an observational trauma database of the level 1 trauma centre at Innsbruck Medical University hospital. Trauma patients (≥18 years) with multiple injuries and an Injury Severity Score ≥17 were included and analysed. Results: In total, 279 patients were analysed, of which 42 patients (15.1%) died. With increasing blood glucose upon hospital admission, the rate of patients with haemorrhagic shock rose significantly [from 4.4% (glucose 4.1–5.5 mmol/L) to 87.5% (glucose >15 mmol/L), p < 0.0001]. Mortality was also associated with initial blood glucose [≤5.50 mmol/L 8.3%; 5.51–7.50 mmol/L 10.9%, 7.51–10 mmol/L 12.4%; 10.01–15 mmol/L 32.0%; ≥15.01 mmol/L 12.5%, p = 0.008]. Admission blood glucose was a better indicator for haemorrhagic shock (cut-off 9.4 mmol/L, sensitivity 67.1%, specificity 83.9%) than haemoglobin, base excess, bicarbonate, pH, lactate, or vital parameters. Regarding haemorrhagic shock, admission blood glucose is more valuable during initial patient assessment than the second best predictive parameter, which was admission haemoglobin (cut-off value 6.5 mmol/L (10.4 g/dL): sensitivity 61.3%, specificity 83.9%). Conclusions: In multiple trauma, non-diabetic patients, admission blood glucose predicted the incidence of haemorrhagic shock. Admission blood glucose is an inexpensive, rapidly and easily available laboratory value that might help to identify patients at risk for haemorrhagic shock during initial evaluation upon hospital admission.